DUVERGER´S LAWS FROM MICROSCOPIC VIEW - Radek Svec (European Scientific Journal, ESJ, 2014)
This article deals with the problematic of relationship between electoral and party systems. Its based on theory of Maurice Duverger and Giovanni Sartori, but it takes the influence of electoral systems from microscopic view rather than from macroscopic view. It shows three different electoral systems – plurality, two round plurality and proportional representation, in three different countries – Germany, Great Britain and France, and influence of electoral systems to the party system, especially to small and new parties. It works with the theory of barriers, that parties has to overcome to become relevant – barrier to legislature and barrier to executive.